KAJIAN PENGEMBANGAN FASILITAS LAYANAN POLIKLINIK ANAK RUMAH SAKIT IMMANUEL TERHADAP TINGKAT KEBUTUHAN DAN LOYALITAS PELANGGAN - Ancilla Lina (Jurnal Ilmu Kesehatan Immanuel, 2024)
Facing the realities surrounding healthcare services in Indonesia, it cannot be denied that the old paradigm of healthcare services needs to be overhauled to ensure the continued existence of hospitals. The complexity of the issues faced by hospitals necessitates hospital management that is capable of managing and providing the best services. The aim of this research is to determine patients' perceptions of various healthcare services, the gap between performance and perceived importance levels, and the level of patient loyalty to healthcare services provided at the Immanuel Hospital Children's Clinic. The research was conducted using descriptive methods and Stratified Random Sampling techniques. The results of the research show that patients give favorable ratings (55.73%) to the various healthcare services at the Children's Clinic, there is still a gap between customer expectations and the clinic's performance, and customers demonstrate loyalty to the clinic. Keywords: Development polyclinic, loyality and customer needs.